Bus Rapid Transit (BRT) system impacts to environmental quality - Bakeri, Mohamad Haniff; Che Ahmad, Amalia; Abdul Tharim, Asniza Hamimi (2013)
Sustainable Urban Transport Research Centre (SUTRA), Universiti Kebangsaan Malaysia, Environmental Quality is an indicator of regional quality of life, supporting the health and well-being of the public and the attractiveness and sustainability of the urban and natural environment. Transit agencies are adopting vehicles with alternative fuels, propulsion systems, and pollutant emissions controls.When discussing tansportation systems, the primary way to improve the environment is through reduction of vehicular emissions to improve air quality.There are two broad categories of emissions according to the scope of impact- local or criteria pollutants and global pollutants. Local or criteria pollutants include nitrogen oxides, sulfur oxides, carbon monoxide, volatile organic compounds, lead, and particulate matter of various sizes; and global pollutants include carbon dioxide and other greenhouse gases.The primary advantage of Bus rapid 'Transit (RRT) technology is that it can be adapted to a multitude of operating environments, with sufficient scalability to deliver increased carrying capacity to meet future ridership growth.This research focuses mostly on the reduction of emissions of air pollutants from BRT investments since it usually has the most direct impact on urban environments.